(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
The concept of marketing activity refers to a bank’s consumer-oriented philosophy and strategy, aimed at achieving its goals. This concept is grounded in the analysis of a comprehensive set of indicators that influence the financial and credit system as a whole, and the bank in particular. Based on the marketing concept, proposals are developed to optimize the bank’s operations, with a comprehensive planning process for both its internal and external activities. The marketing concept chosen is based on the most important market indicators, which are incorporated into calculations, depending on the bank’s specific characteristics (size, operational features, founders) and its goals and objectives.